Location-Price Competition in Airline Networks - H. Gao; J. Hu; V. Mazalov; A. Shchiptsova; L. Song; J. Tokareva (Journal of Applied Mathematics)
This paper addresses location-then-price competition in airline market as a two-stage game of n players on the graph. Passenger’s demand distribution is described by multinomial logit model. Equilibrium in price game is computed through best response dynamics. We solve location game using backward induction, knowing that airlines will choose prices from equilibrium for the second-stage game. Some numerical results for airline market under consideration are presented.